A new method for the determination of sulphide in gastrointestinal contents and whole blood by microdistillation and ion chromatography - Richardson, Caroline J; Magee, Elizabeth A.M; Cummings, John H (Clinica chimica acta, 2000)
Hydrogen sulphide is produced in the human large intestine by the bacterial reduction of dietary inorganic sulphate and sulphite and by fermentation of sulphur amino acids. Sulphide may damage the colonic epithelium and has been implicated in the pathogenesis of ulcerative colitis. The accurate measurement of sulphide in biological samples, particularly in gut contents is difficult due to the volatile nature of the compound, and the viscosity and turbidity of the samples. Here we describe a method for the determination of sulphide in gut contents and whole blood which overcomes these problems. Initially, samples are treated with zinc acetate to trap sulphide. A microdistillation pretreatment is then used, which releases sulphide from its stable, stored state, coupled to ion chromatography with electrochemical detection. The limit of detection of the method was determined as 2.5 μmol/l, which enabled sulphide levels in gut contents and whole blood samples obtained from humans to be accurately determined. A preliminary investigation in healthy human subjects showed blood sulphide ranged from 10 to 100 μmol/l. Whole blood sulphide did not change significantly when increasing amounts of protein from meat were fed. However, faecal sulphide did show a significant increase from 164 to 754 nmol/g in four subjects fed diets which contained 60 and 420 g meat.